Postsecular Conflicts Debating tradition in Russia and the United States - Stoeckl, Kristina; Uzlaner, Dmitry (Edited Volume Series, 2020)
In the globalizing culture wars of the twenty-first century, Americans are discovering Russia as a new haven of traditionalism and Russian conservatives are re-inventing themselves as the traditionalist leaders of the world. While American and Russian conservatives reach out to each other, liberal critics and moderate Orthodox put this new alliance into question and reclaim tradition from the traditionalists. This edited volume gathers interviews and original essays for a confrontational debate about the meaning of religion, tradition, and liberalism in Russia and in the United States.; In den sich globalisierenden Kulturkriegen des 21. Jahrhunderts entdecken die Amerikaner Russland als neuen Hafen des Traditionalismus und die russischen Konservativen erfinden sich als traditionalistische Führer der Welt neu. Während sich amerikanische und russische Konservative gegenseitig unterstützen, stellen liberale Kritiker und gemäßigte Orthodoxe dieses neue Bündnis in Frage und fordern die Tradition der Traditionalisten zurück. Dieser Band enthält Interviews und Essays für eine Debatte über die Bedeutung von Religion, Tradition und Liberalismus in Russland und den Vereinigten Staaten.